Pendampingan Pembuatan Perangkat Pembelajaran Berbasis Proyek Penguatan Profil Pelajar Pancasila (P5) Pada Guru Di Kalisat - Indah Rahayu Panglipur; Eric Dwi Putra; Sunardi Sunardi; Erfan Yudianto (Jurnal Kabar Masyarakat, 2023)
The program This education mentoring program is an ongoing effort in which different stakeholders work together to achieve the goal of better education for the community. for the Community The school curriculum based on the project of strengthening the profile of pencasila learners (P5) has been implemented in the aftermath of the pandemic. It is necessary to provide assistance in making tools to prospective teachers. The condition of teachers in the school The condition of teachers in the school is still only 20% who have understood the implementation of the P5 while the rest still do not understand P5 at all. The purpose of this activity is to provide provisions and assist teachers to be able to develop appropriate learning tools. appropriate learning tools. One of the benefits that teachers get from this mentoring activity is refreshing their knowledge. knowledge refreshing. This benefit has a positive impact and will definitely improve the quality of the school in the future. school in the future